VENOUS THROMBOEMBOLISM RISK ASSESSMENT IN HOSPITALISED PATIENTS IN A TERTIARY CARE HOSPITAL IN PAKISTAN - Ajwad Farogh; Noman Ullah Wazir; Saima Mumtaz; Farzana Salman; Ahsan Arif; Anam Umair (Journal of Ayub Medical College Abbottabad, 2024)
Background: Venous thromboembolism (VTE) ranks as the third most common cause of vascular death following myocardial infarction and stroke. VTE is a prevalent illness, particularly in the elderly, and is linked to a high recurrence rate, substantial healthcare costs, and reduced survival rates. The Objective of the study was to investigate the impact of using the VTE risk assessment (VTE-RA) tool and thromboprophylaxis (TP) on all adult patients hospitalized. Methods: This study was conducted at a single centre using a prospective cross-sectional design to compare data before and after an intervention at a tertiary referral hospital in Pakistan from May 2019 to February 2020. All adult inpatients over the age of 18 were eligible for inclusion. Results: A total of 1,200 patients were screened in the study. The majority of these patients were medical 701(58.42%) and 499(41.58%) were surgical. The mean age of patients was 59.02±1.40 years. The male patients were 690(57.55%) as compared with females were 510 (42.5%). The average stay in hospital was 8.01±1.11 days. At that time, there was no official RA instrument implemented. Researchers documented any written proof of RA in patients’ medical records as "RA completed." 190(15.83%) out of all charts evaluated had a recorded VTE risk assessment. TP was prescribed to 450(37.5%) patients, which accounts for of the total. Risk factors for VTE in high-risk patients. Conclusion: VTE risk assessment, prescribing adequate thromboprophylaxis, and integrating it into practice is challenging. The majority of hospitalized patients investigated were at a high risk of having venous thromboembolism (VTE). The most prevalent risk factor for developing VTE is old age, however, only few hospitalized patients were actually given thromboprophylaxis.